Exploring Aftercare Experiences and Well-Being after Completion of a Young Adult Addiction Treatment Program. Issue 2 (3rd April 2023) - Russell, Keith C.; Gillis, Harold. L. (Lee)
ABSTRACT: Adventure therapy (AT) interventions are being integrated with evidence-based treatment models for a variety of clients, including adolescents and young adults, for a wide range of presenting symptomology, including substance use disorders (SUD). Though some studies have explored longer term outcomes, little is known about the posttreatment experiences of clients. Clients from a 90-day AT treatment program were contacted approximately posttreatment and asked to assess their general well-being and current relationship with substance use. Results showed that clients were doing well evidenced by OQ-45 scores that were statistically similar at the discharge and follow-up period ( t (92) = −1.693, p < .09; Cohen's d = −.180). Clients also showed statistically significant increases in mindfulness skills. Results also showed that 70.8% of the participants indicated that they did relapse, while 29.2% indicated they did not. Of those that relapsed, 73.8% indicated the relapse was "severe, " while 26.3% believed their relapse was "not severe." Clients reflected favorably on their treatment experience and desired more structured aftercare opportunities posttreatment. Implications for professional practice and research include the need to advance perspectives of recovery and develop aftercare support systems that can aid clients in the recovery process.